Sources of Macroeconomic Fluctuations in Iran Focusing on Real Exchange Rate: 1970-2005 - Kiumars Aghaei; Amir Jabbari; Mohammad Karimi (پژوهشهای اقتصادی, 2008)
Recent discussions on macroeconomic policy in developing and developed countries have emphasized the crucial role played by the real exchange rate in the adjustment process. There is a growing agreement that sustained real exchange rate misalignment will usually generate severe macroeconomic disequilibria through affecting macroeconomic variables. This study aims to investigate the sources of macroeconomic variable fluctuations in Iran focusing on real exchange rate. We implement the model with a structural VAR model and variance decomposition technique using annual macroeconomic time series data of the Iranian economy from 1970 to 2005. The findings suggest that real exchange rate fluctuations in Iran are mostly explained by monetary shocks as well as oil price shocks. Moreover, the results show that major part of income fluctuations in Iran are due to the price shocks, oil price shocks, money shocks, and supply shocks. This paper recommends that diversifying the economy, developing infrastructure, stabilizing prices, increasing investment, reducing money fluctuations, and controlling money supply may well then contribute to improve growth performance in the economy. According to our results, money disturbances and oil prices effect significantly real exchange rate fluctuations. So, this paper suggests that conducting monetary policy requires a greater caution to stabilize the economy.